A Scoping Review of the Trauma Recovery and Empowerment Model (TREM). (July 2022) - Masin-Moyer, Melanie; Kim, Jessica Cho; Engstrom, Malitta; Solomon, Phyllis
The link between interpersonal trauma and negative biopsychosocial outcomes has been well-documented. Integrated treatments that address trauma, mental health, and substance use among women with trauma histories have been found to be more effective than treatments that focus separately on these concerns. Since the early 2000s, the Trauma Recovery and Empowerment Model (TREM) has been described as a "promising" integrated trauma group therapy for women. Despite widespread recognition and implementation of TREM, its effectiveness has not been clearly established. The present scoping review is the first systematic effort to describe the extant literature on TREM and aims to provide an understanding of TREM's effectiveness by organizing and synthesizing the available empirical data. Guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews, a systematic search was conducted using PubMed, PsycINFO, SW Abstracts, Scopus, Embase, and Web of Science. Quantitative dissertation findings not published elsewhere and peer-reviewed journal articles published in English that reported outcomes from TREM intervention research with adult women were included. Twelve of the initial 385 publications identified met the inclusion criteria and reported data from nine studies. TREM demonstrated statistically significant effects on posttraumatic stress disorder, anxiety, psychological/psychosomatic distress, and substance use. A more limited set of findings suggests that TREM may also be associated with additional gains, including self-esteem, relationship power, social support, attachment, and spiritual well-being. Future research should replicate findings, use random assignment to groups, involve larger sample sizes and more representative samples, examine optimal duration, and identify components that facilitate change.